Optical Dispersion Parameters of (PMMA doped red methyl) Irradiated by Gamma Rays (Journal of the College of Basic Education, 2023)
The dispersions of the refractive indices of (PMMA doped red methyl) films Irradiated by Gamma Rays have been determined using the Wemple-DiDomenico model . The oscillator energy E0 , dispersion energy Ed , absorption coefficient and skin depth are calculated before and after irradiated . Drude’s theory of dielectrics used to calculate carrier concentration Nopt . It's found that Nopt increases after irradiation .